2013
DOI: 10.1007/s00270-013-0586-2
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Pelvic Congestion Syndrome: Visual Analog Scale (VAS) Long-Term Follow-up Clinical Evaluation in 202 Patients

Abstract: Coil embolization of PCS is an effective and safe procedure, with high clinical success rate and degree of satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
114
0
21

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(141 citation statements)
references
References 23 publications
6
114
0
21
Order By: Relevance
“…Кроме того, ряд авторов [7,8] сообщают о таких осложнениях эмбо лизации гонадных вен, как протрузия спиралей в за брюшинное пространство, развитие забрюшинной гематомы и миграция металлических окклюторов в легочное артериальное русло. До конца не ясным остается причина сохранения либо усиления ХТБ у пациенток после эндоваскулярного вмешательства при отсутствии патологического рефлюкса крови ниже уровня окклюзии гонадных вен.…”
Section: Discussionunclassified
“…Кроме того, ряд авторов [7,8] сообщают о таких осложнениях эмбо лизации гонадных вен, как протрузия спиралей в за брюшинное пространство, развитие забрюшинной гематомы и миграция металлических окклюторов в легочное артериальное русло. До конца не ясным остается причина сохранения либо усиления ХТБ у пациенток после эндоваскулярного вмешательства при отсутствии патологического рефлюкса крови ниже уровня окклюзии гонадных вен.…”
Section: Discussionunclassified
“…Certain complications were reported with diff erent frequencies such as stent migration to the right atrium, protrusion to the IVC or stent thrombosis [17,18]. Endovascular embolisation of the ovarian vein with coils and sclerosans is a standard approach in the treatment of symptomatic pelvic venous insuffi ciency [4], but in patients with NCS and PVCS, it has been mentioned only sporadically in the literature. Hartung et al reported the experience of left ovarian embolisation in PVCS, where NCS was not initially diagnosed and patients developed recurrent symptoms after 2 -3 months [18].…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal imbalance, valvular insuffi ciency or venous obstruction may cause PVCS. Primary PVCS has nonobstructive causes, while secondary develops when pelvic and ovarian veins serve as a collateral pathway that relieves upstream obstruction, as in May-Turner syndrome or NCS [4]. In some opinions, the nutcracker anatomy is an overstated cause of a left ovarian varicocele [5].…”
Section: Discussionmentioning
confidence: 99%
“…They analyzed 12 studies and the results showed significant relief from symptoms, varying from 50 to 100. Laborda et al 11 followed 202 patients for five years with repeated assessments and observed a reduction in visual pain scale scores from 7.34 ± 0.7 (preoperative) to 0.78 ± 1.2 (5 years later). An earlier study conducted by Kim et al 12 with 127 patients and a similar design reported comparable preoperative visual pain scale scores (7.6 ± 1.8), but the results observed during follow-up were less significant, with a mean score of 2.9 ± 2.8.…”
Section: Discussionmentioning
confidence: 99%